Studies on eimeriosis in birds. Observations regarding the etiology - Brada, Wilhelm (Pesquisa Agropecuaria Brasileira, 2024)
The author describes the results of his observations on eimeriosis in the small intestine of poultry and of the digestive tract of turkeys, pigeons and ducks. During these studies the author found in 6 to 8 weeks old chickens one species of Eimeriae which differed in the morphological characteristics of the oocysts from those of known species of Coccideae of poultry. The author succeeded in infecting chickens with only one oocyst of Eimeria tenella. This shows the great danger of propagation of the disease, even when small numbers of oocysts are ingested. In experiments performed at the same time, the author studied the maintenance of virulence of E. tenella and E. necatrix. He found that their oocysts, when kept in water, keeps their capacity of infestation for two years and two months or for one year and two months, respectively.